The Quality of Life among Patients with Lyme Disease – a Cross Sectional Study - Daria Jucha; Ewelina Kolarczyk; Joanna Żółtańska; Bogusława Banaszak-Żak; Agnieszka Młynarska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Quality of life plays an important role in the fields of health and medicine.